Can Task-Switching Training Enhance Executive Control Functioning in Children with Attention Deficit/-Hyperactivity Disorder? - Kray, Jutta; Karbach, Julia; Haenig, Susann; Freitag, Christine (Frontiers in Human Neuroscience, 2012)
The key cognitive impairments of children with attention deficit/-hyperactivity disorder (ADHD) include executive control functions such as inhibitory control, task switching, and working memory. In this training study we examined whether task-switching training leads to improvements in these functions. Twenty children with combined type ADHD and stable methylphenidate medication performed a single-task and a task-switching training in a crossover training design. The children were randomly assigned to one of two groups. One group started with the single-task training and then performed the task-switching training and the other group vice versa. The effectiveness of the task-switching training was measured as performance improvements (relative to the single-task training) on a structurally similar but new switching task and on other executive control tasks measuring inhibitory control and verbal working memory as well as on fluid intelligence (reasoning). The children in both groups showed improvements in task switching, that is, a reduction of switching costs, but not in performing the single tasks across four training sessions. Moreover, the task-switching training lead to selective enhancements in task-switching performance, that is, the reduction of task-switching costs was found to be larger after task-switching than after single-task training. Similar selective improvements were observed for inhibitory control and verbal working memory, but not for reasoning. Results of this study suggest that task-switching training is an effective cognitive intervention that helps to enhance executive control functioning in children with ADHD.